PROBLEMATIQUE DE LA COUVERTURE DES CHARGES DE CONSOMMATION AU SEIN DES MENAGES DES AGENTS ET FONCTIONNAIRES DE L’ETAT EN PROVINCE DE LA SHOPO - Joseph ISEGE SHINDANO, (IJRDO - Journal of Business Management, 2021)
To identify the mechanism by which the majority of the servants and civils servant of the Provincial Division of the Infrastructures and Public working in Kisangani, remunerated Congolese francs resort to cover the entirety of the consumer expenditure within their households is the motivation which made that we can choose this topic.Taking account of the diversity of answers provided by our surveyed to our concern during the phase of pre investigation, we supposed that the majority of our surveyed would assign the totality of their monthly incomes to consumption, supplemented by the loans near the moneychangers, refundable with interests at the varying rate from 30% to 50%.However, it comes out from our results that, contrary to our principal assumption, the majority of our surveyed resort rather to the protective sackings (31 subjects among the 50, is 62%), because the loans near the refundable moneychangers with interests account for only 24%.